1996
DOI: 10.1099/13500872-142-3-459
|View full text |Cite
|
Sign up to set email alerts
|

High cAMP Levels Antagonize the Reprogramming of Gene Expression that Occurs at the Diauxic Shift in Saccharomyces Cerevisiae

Abstract: cAMP and gene expression in S. cerevisiae yeast, Ras proteins are controlling elements of adenylate cyclase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
86
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 43 publications
9
86
0
1
Order By: Relevance
“…Yeast strains and media: The S. cerevisiae strains used for this work are OL556 (MATa/MATa, cdc25-5/cdc25-5 his3/his3 leu2/ leu2 trp1/TRP1 rca1/rca1 ura3/ura3) (Boy-Marcotte et al 1996), 74D694 (MATa ade1-14 trp1-289 leu2-3,112 his3-200 ura3-52) ½psiÀ; ½psi1 (Derkatch et al 1998), MT557/3b (MATa ade2-1 sup45-2 leu2-3,112 ura3-1 his5-2) (Stansfield et al 1995a), and FS1 (MATa, ade2-592 lys2-201 leu2-3,112 his3-200 ura3-52) (Namy et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Yeast strains and media: The S. cerevisiae strains used for this work are OL556 (MATa/MATa, cdc25-5/cdc25-5 his3/his3 leu2/ leu2 trp1/TRP1 rca1/rca1 ura3/ura3) (Boy-Marcotte et al 1996), 74D694 (MATa ade1-14 trp1-289 leu2-3,112 his3-200 ura3-52) ½psiÀ; ½psi1 (Derkatch et al 1998), MT557/3b (MATa ade2-1 sup45-2 leu2-3,112 ura3-1 his5-2) (Stansfield et al 1995a), and FS1 (MATa, ade2-592 lys2-201 leu2-3,112 his3-200 ura3-52) (Namy et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The changes in protein synthesis during the diauxic shift were also investigated. Two-dimensional gel electrophoresis showed that many proteins are affected (6,7). These large scale analyses showed the complexity of the regulations occurring at the diauxic shift.…”
mentioning
confidence: 99%
“…Indeed, it has been shown that the signal that coordinately regulates carbon and nitrogen metabolism in Escherichia coli depends on the intracellular levels of ␣-ketoglutarate and glutamine (15). Interestingly, the presence of Gdh3p has been found to be increased during diauxic transition in S. cerevisiae (16), suggesting a particular role of this enzyme in respiratory metabolism.…”
mentioning
confidence: 99%